2020
DOI: 10.1111/asj.13459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pineapple stem starch feeding on rumen microbial fermentation, blood lipid profile, and growth performance of fattening cattle

Abstract: Corn and cassava are readily available and are the most popular starch sources in Thailand and other Southeast Asian countries. However, the cost of these starch sources has risen due to increasing interest in their use for animal feed, especially in ruminant livestock. Indeed, corn and cassava as ruminant feed ingredients have become highly competitive (Wanapat et al., 2012). On the other hand, byproducts of agricultural and pharmaceutical industries have replaced some corn and cassava recently. One such bypr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In our previous study, the PS contained in the diet did not affected rumen pH but increased total SCFA, ADG, and weight gain. The current study showed that PS tended to produce a higher ADG than for GC (Khongpradit et al 2020). Animal weight gain is usually due to the ingestion of nutrients that are subsequently digested in the gut; thus, feed e ciency is based on the properties of the feed ingredients (Svihus et al 2005, Stevnebø et al 2009).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In our previous study, the PS contained in the diet did not affected rumen pH but increased total SCFA, ADG, and weight gain. The current study showed that PS tended to produce a higher ADG than for GC (Khongpradit et al 2020). Animal weight gain is usually due to the ingestion of nutrients that are subsequently digested in the gut; thus, feed e ciency is based on the properties of the feed ingredients (Svihus et al 2005, Stevnebø et al 2009).…”
Section: Discussionmentioning
confidence: 62%
“…The fermentation products formed due to the interaction between the microbes and the diet produced SCFA, lactic acid, or other organic acids that resulted in a decreased ruminal pH and this may affect ruminal health (Castillo-González et al 2014). Notably, in our previous study, a diet rich in pineapple stem starch resulted in a normal range in ruminal pH (Khongpradit et al 2020). Thus, it is suggested that PS at a high ratio has potential for use as a soluble carbohydrate source in the diet of a ruminant without a risk to the animal's health.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Frozen 1.5-cm-thick subsamples from 14 and 21 days post-mortem were pulverized through cryogenic grinding using a micro-Waring Blender (50-250 mL). One gram of the pulverized muscle sample was homogenized in 6 mL of cold 0.6 M perchloric acid at 23,000 g for 10 s (T25 Ultra-Turrax ® , Ika, Staufen, Germany) according to [15]. After cooling for 15 min, the homogenate was neutralized with 5.4 mL of 0.8 M KOH and 0.25 mL of KH 2 PO 4 buffer.…”
Section: Ribonucleotide Analysismentioning
confidence: 99%
“…(2020) [15] reported the higher degradability of PI starch in the rumen resulting in higher weight gain, average daily gain and feed conversion ratio in PI-fed steers compared to COand CA-fed steers. However, the different sources of starch in the concentrate ration did not affect the intramuscular fat content, as indicated by the similar amount of total fatty acids in the present study.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%